Unusual reflection of electromagnetic radiation from a stack of graphene layers at oblique incidence - Bludov, Yuliy V. (2013)
We study the interaction of electromagnetic (EM) radiation with single-layer graphene and a stack of parallel graphene sheets at arbitrary angles of incidence. It is found that the behavior is qualitatively different for transverse magnetic (or p-polarized) and transverse electric (or s-polarized) waves. In particular, the absorbance of single-layer graphene attains a minimum (maximum) for the p (s)-polarization at the angle of total internal reflection when the light comes from a medium with a higher dielectric constant. In the case of equal dielectric constants of the media above and beneath graphene, for grazing incidence graphene is almost 100% transparent to p-polarized waves and acts as a tunable mirror for the s-polarization. These effects are enhanced for a stack of graphene sheets, so the system can work as a broad band polarizer. It is shown further that a periodic stack of graphene layers has the properties of a one-dimensional photonic crystal, with gaps (or stop bands) at certain frequencies. When an incident EM wave is reflected from this photonic crystal, the tunability of the graphene conductivity renders the possibility of controlling the gaps, and the structure can operate as a tunable spectral-selective mirror.